Linking the Braden Scale to the International Classification of Functioning, Disability and Health. - Fontana, Mariane Benicio; Paiva, Rebeca Fernandes Rocha; Santos, Bárbara Cordeiro; Sharan, Karoleen Oswald; Moser, Auristela Duarte de Lima; Shmeil, Marcos Augusto Hochuli (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Pressure ulcers (PU) are defined as an injury to the skin and / or underlying tissue, resulting of pressure or combination of pressure and torsional strength. Its occurrence can be prevented by establishing protocols with risk assessment and preventive measures. The Braden Scale is a tool for assessing risk of developing PU. The International Classification of Functioning, Disability and Health (ICF), in turn, provides a scientific basis for the study of health and conditions related to it, as well as be used to guide the creation and the use of outcome measures in rehabilitation. Objective: To relate the contents of the Braden Scale with the contents of ICF. Method: The present study was exploratory descriptive. The content of the Braden Scale was linked to the content of the ICF, using rules proposed in the literature. Four health professionals participated in the linking process. Results: Twenty-nine meaningful concepts were identified in the Braden Scale. From this total, 21 were linked to 17 ICF categories, 6 were classified as nd (not definable) and 2 were classified as nc (not covered by ICF). None of the significant concepts of the Braden Scale was related to some category of the component Body Structures of ICF. Conclusion: The content of the Braden Scale showed a moderate convergence with the contents of the ICF, being possible to consider that this scale is within the biopsychosocial model of health. These results place the Braden Scale as a possible tool to be used to assist in the implementation of the ICF in patients at risk of developing PU.